THE USE OF AUTHENTIC MATERIALS IN TEACHING LISTENING AT SENIOR HIGH SCHOOL - Aryuliva Adnan (International Conference on Languages and Arts, 2013)
Among the four skills (listening, speaking, reading and writing) that are recognized as the keys to ‘knowing’ the language, listening is probably the least important to be taught. Actually speaking and listening are always interrelated. However listening is the most “underdeveloped” skill. Basically, they realize that listening cannot be separated from other language skills like speaking, reading and writing. Listening is important since students may receive much of their information of their school through listening to instructors and to another. Listening has been regarded as the most frequently used language skills in the classroom. Furthermore nowadays listening skill is inclusive in national examination for the level of Senior High School. In Indonesia the teachers tend to ignore to teach this skill by skipping it even though it is clearly stated in curriculum. The teachers skip teaching listening for many reasons, such as lack of teaching material, lack of school facilities, the speakers in the recorded material speak too fast, the students do not understand the vocabularies and the sentences used by the speakers. The reason of lack of material for teaching of listening nowadays can be minimized, since the teachers can use authentic materials recorded from internet, TV and radio programs. Teachers can select the materials needed for their teaching based on the topic they are going to teach and the level of their students. Therefore teachers have no reasons to ignore and skip teaching of listening, for they can have their authentic teaching materials easily.